2013
DOI: 10.3233/jad-121912
|View full text |Cite
|
Sign up to set email alerts
|

MEG Delta Mapping Along the Healthy Aging-Alzheimer's Disease Continuum: Diagnostic Implications

Abstract: New diagnostic criteria for Alzheimer's disease (AD) stress the role of in vivo biomarkers. Neurophysiological markers are usually not considered as such criteria, although theoretical and practical reasons would justify them. In order to assess the value of neurophysiology as an AD biomarker, whole-head magnetoencephalographic (MEG) resting state recordings were obtained from 35 AD patients, 23 mild cognitive impairment (MCI) patients, and 24 healthy controls. The AD group was further split into two groups di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 0 publications
4
42
0
1
Order By: Relevance
“…Increased power and connectivity of slow wave frequency bands (i.e., theta and beta) has consistently been observed in adult brain injury and disease, including TBI and Alzheimer's disease severity (Fernandez et al, ; Hier et al, ; Huang et al, ). This slow‐wave oscillatory activity has been observed both within and between brain regions (Bajo et al, ; Dunkley et al, ; Hier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased power and connectivity of slow wave frequency bands (i.e., theta and beta) has consistently been observed in adult brain injury and disease, including TBI and Alzheimer's disease severity (Fernandez et al, ; Hier et al, ; Huang et al, ). This slow‐wave oscillatory activity has been observed both within and between brain regions (Bajo et al, ; Dunkley et al, ; Hier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this argument is provided by Fernandez et al [38] in an MEG study that reported increased occipital delta current density in individuals with prodromal AD, with this activity likely reflecting dysfunctional synaptic transmission. In patients who have already progressed to full clinical AD, an increase in both delta and theta oscillations was found in the temporoparietal regions, and this correlated with HA [39].…”
Section: Aging and Cortical Oscillationsmentioning
confidence: 95%
“…Nevertheless, the more important question addressed by our investigation is the potential role of neurophysiological techniques (EEG or MEG) as markers for AD pathology. In a very recent study of our group (Fernandez et al 2013), it was demonstrated that delta current densities in posterior parietal, occipital, prerolandic, and precuneus cortices distinguished among MCI patients, AD patients with different severity scores, and controls. More importantly, an increase in delta activity in posterior regions such as the right posterior parietal cortex and the precuneus indexed the transition from MCI to mild and from mild to more severe dementia.…”
Section: Discussionmentioning
confidence: 99%